IDENTIFICATION OF POTENTIAL AND PLANNING FOR DISASTER RECOVERY USING THE ISO/IEC 24762 STANDARD AT XYZ UNIVERSITY - Devi Yurisccca Bernanda; Yanthi Charolina; Ozmar Azhari; Cynthia Pangrestu; Johanes Fernandes Andry (Universitas Teknokrat Indonesia, 2023)
XYZ University is a college that annually accepts large numbers of students and has tens of thousands of students. This organizations have an obligation to maintain information and maintain the existence of information against various risks of accidents, whether intentional or unintentional. With the possibility of a risk in the form of a disaster which is a threatening and disruptive event, a disaster can cause loss of organizational data so that risk management is needed that can control it. The progress of information technology development has made technology a means to assist disaster recovery plans in tertiary institutions. The Disaster Recovery Plan is a strategic step to restore the system due to the impact of disasters, both natural and non-natural disasters. Disaster Recovery Plan (DRP) is a set of documents that defines every activity, action, and procedure that must be carried out related to disaster recovery, continuing delayed business processes in a short time and can save existing assets. The research was conducted using the ISO / IEC 24763: 2008 standard. The results obtained are in the form of Risk Recapitulation Based on Literature, then the severity and detection levels are obtained through FMEA analysis which is assessed at levels 1-10, and with business impact analysis the RTO and RPO results are obtained.